2020
DOI: 10.1093/ageing/afaa178
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and physical and mental health in the very old: An individual participant data meta-analysis of four longitudinal studies of ageing

Abstract: Objective To determine the physical and mental health of very old people (aged 80+) with anaemia. Methods Individual level meta-analysis from five cohorts of octogenarians (n = 2,392): [NZ study] Māori, [NZ study] non-Māori, [NL study], [UK study], and [JP study]. Mixed models of change in functional ability, cognitive function, depressive symptoms, and self-rated health over time were separately fitted for each cohort. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…This study showed that a combination of determinants of anaemia is associated with the presence and development of anaemia in the very old. Since anaemia in the very old is common and associated with poor outcomes [ 43 ], health professionals need to be aware that individuals over 85 years of age with a combination of determinants of anaemia present with a high risk of prevalent and incident anaemia. However, further research is needed to explore the underlying pathophysiological mechanisms, either on the specific combinations of determinants, or on the effects within different ethnicities and in younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that a combination of determinants of anaemia is associated with the presence and development of anaemia in the very old. Since anaemia in the very old is common and associated with poor outcomes [ 43 ], health professionals need to be aware that individuals over 85 years of age with a combination of determinants of anaemia present with a high risk of prevalent and incident anaemia. However, further research is needed to explore the underlying pathophysiological mechanisms, either on the specific combinations of determinants, or on the effects within different ethnicities and in younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 contains the flow chart of study identification. We included 18 publications of IPD-MA of NRSs evaluating continuous outcomes (12,13,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), more than half (61%) published since 2018. Table 1 lists the characteristics of the studies we included: 10 (56%) used change score; seven (39%) used ANCOVA, and one (5%) used propensity score.…”
Section: Systematic Review Of Ipd-mas Of Nrssmentioning
confidence: 99%
“…While typically mild, anemia negatively impacts physical and cognitive function, depression, and self-rated health status. 70 Although there is no conclusive evidence that the treatment of anemia has a positive impact on any of the associated adverse outcomes, 51 novel agents, such as hypoxia-inducible factor stabilizers, hepcidin modulators and activin type II receptor agonists, are being introduced in the clinical setting. 71 With an increased understanding of the etiology of anemia and the availability of innovative anti-anemic drugs, future research will assess the potential benefits of therapeutic interventions for anemia in terms of quality of life and reduced morbidity and mortality, along with further investigation of the causes of unexplained anemia.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Anemia is common in older persons, and is associated with frailty, [1][2][3] falls, 4 cognitive decline, [5][6][7] depression, 6 worsening functional ability 6 and early mortality. 8 The definition of anemia in adults was proposed by the World Health Organization (WHO) more than 50 years ago among a cohort of people aged >65 years, where anemia was defined as hemoglobin (Hb) level <13.0 g/dL in men and <12.0 g/dL in women.…”
Section: Introductionmentioning
confidence: 99%